2013
DOI: 10.1002/chin.201350151
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Synthesis of Some Novel Chalcones, Flavanones and Flavones and Evaluation of Their Antiinflammatory Activity.

Abstract: Activity. -The anti-inflammatory activity of a series of novel synthesized chalcones (III), flavones (V) and flavanones (IV), derived from 2-hydroxyacetophenones and aromatic aldehydes is presented. The tested compounds, especially compound (IIId), show good in vitro anti-inflammatory activity compared to the reference drug indomethacin. -(BANO, S.; JAVED, K.; AHMAD, S.; RATHISH, I. G.; SINGH, S.; CHAITANYA, M.; ARUNASREE, K. M.; ALAM*, M. S.; Eur. J. Med. Chem. 65 (2013) 51-59, http://dx.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 1 publication
0
5
0
2
Order By: Relevance
“…Five novel 3,5-diaryl-2-pyrazoline (2aee) as well as five 3,5-diaryl-2-isoxazoline (4aee) were synthesized by the condensation of chalcones/flavanones with hydrazine hydrate and hydroxylamine hydrochloride respectively. Three novel 3-aroyl-4-aryl-2-pyrazolines 6aec were synthesized by treatment of appropriate chalcones with freshly prepared diazomethane gas dissolved in ether at 0 C. Reaction between synthesized chalcones/flavanones and 4-hydrazinobenzenesulfonamide hydrochloride in ethanol led to synthesis of pyrazolines bearing sulphonamide moiety (3aeh) as reported earlier [11]. All the synthesized compounds were characterized by IR, 1 H NMR, 13 C NMR, mass and elemental analysis.…”
Section: Chemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…Five novel 3,5-diaryl-2-pyrazoline (2aee) as well as five 3,5-diaryl-2-isoxazoline (4aee) were synthesized by the condensation of chalcones/flavanones with hydrazine hydrate and hydroxylamine hydrochloride respectively. Three novel 3-aroyl-4-aryl-2-pyrazolines 6aec were synthesized by treatment of appropriate chalcones with freshly prepared diazomethane gas dissolved in ether at 0 C. Reaction between synthesized chalcones/flavanones and 4-hydrazinobenzenesulfonamide hydrochloride in ethanol led to synthesis of pyrazolines bearing sulphonamide moiety (3aeh) as reported earlier [11]. All the synthesized compounds were characterized by IR, 1 H NMR, 13 C NMR, mass and elemental analysis.…”
Section: Chemistrymentioning
confidence: 99%
“…The new substituted pyrazolines and isoxazolines in addition to eight previously reported pyrazolines bearing benzenesulfonamide moiety [11] were screened for their antibacterial and antifungal activities. Our group has earlier reported the anti-inflammatory and anti-cancer profile of pyrazolines bearing benzenesulfonamide moiety [11]. The molecular docking study of all the compounds has been done for the better understanding of the drug-receptor interaction.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14][15] Recently, it was reported that N-substituted cyclic imide derivatives afforded a new scaffold for small molecule COX-2 inhibitors which should offer opportunities for various kinds of structural development. [16]In addition to this, N-substituted cyclic imide derivatives possess remarkable anti-inflammatory activity through inhibition of tumor necrosis factor alpha (TNF-α) and interleukin-6 (IL-6).…”
Section: Introductionmentioning
confidence: 99%
“…[23][24][25]Moreover, among the highly marketed COX-2 inhibitors that comprise the sulfonamide moiety, celecoxib and SC-558 ( Fig.1) are the major determinant for COX-2 selectivity and invivo efficacy. [13,15,26]Promising anti-inflammatory activity of some maleimide as well as sulfonamide derivatives (Fig.2) prompted us to investigate them further. However, a maleimide ring has not been appearing to be linked with benzenesulfonamide so far.…”
Section: Introductionmentioning
confidence: 99%
“…Chalcones are 1, 3-diaryl-2-propen-1-ones possessing a diverse range of biological activities including anticancer [9,10], antimicrobial [11,12], anti-HIV [13,14], anti-oxidant [15,16], antiinflammatory [17,18] and anti-protozoal activities [19,20]. Modification in their structure leads to an enhancement in their biological activity and therapeutic efficacy [21].…”
Section: Introductionmentioning
confidence: 99%